Rules for investigation of patients with asymptomatic elevation of serum aminotransferase activity - M. V. Mayevskaya; V. T. Ivashkin; Ye. N. German (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Publication is intended for clinicians dealing with patients who have abnormal blood biochemical tests. Nowadays investigation of blood biochemistry scores, which reflect functional state of body organs and systems, deeply settled in medical practice. Correct understanding of these results helps to diagnose, stage the disease, prescribe treatment and control its efficacy. Features of differential diagnosis and medical approach in patients without any clinical symptoms is actual and common issue faced by many general practitioners every day. As a rule, elevation of activity of alanine and-or aspartate aminotransferases (ALT, AST) is considered as highly significant marker of hepatocyte damage. However, it is necessary to remember, that far from all patients with raised level of aminotransferases have serious liver diseases. More often doctor should interpret elevation of level of ALT and-or AST in patients with obesity, diabetes mellitus, disorder of lipid metabolism or in the case of absence of clinical symptoms of any disease. In presented article issues of patient management with asymptomatic elevation of ALT and AST activity are covered both general-theoretical, and practical points of view. Screening markers and specifying diagnostic tests are necessary to diagnose correct the majority of liver diseases – viral hepatites, alcoholic (ALD) and non-alcoholic fatty liver diseases (NAFLD), autoimmune hepatitis (AIH), Wilson diseases, primary hemochromatosis etc. States at which in absence of primary liver disease levels of ALT and AST can raise are described.